Antimicrobial and Cytotoxicity Studies of the Aerial Part of Arachis hypogea Linn. (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Arachis hypogea; Papilionaceae; Cytotoxicity; AntimicrobialDOI: http://dx.doi.org/10.3329/sjps.v3i2.8034 S.J. Pharm. Sci 3(2): 25-28